Estudo sobre os usos de mecanismos de coesão referencial na produção escrita de alunos de 5ª série. - Corrêa, Arlete Amaral (2010)
This paper is the result of a research that was carried out with fifth graders in a city school in Rio Grande, RS, in 2008. The study aims at describing and analyzing the use of referential cohesion elements in 48 texts written by eight students. These texts were based on the reading of four books that had been previously chosen: O menino do dedo verde (writing/rewriting), Veneno lento (writing/rewriting), A bolsa amarela and A luz que guia também pode cegar . The cohesive categories under analysis are: synonymous or quasi-synonymous expressions, identical lexemes, and ellipsis. The chapter on the theoretical basis comprises three sections: teaching Portuguese in elementary school, teaching grammar in school, and the text in the class. In order to analyze the data, while reading their summaries, I took into account how students referred to the main character in every book they had read. Results show that, after the development of a teaching proposal that was based on the triad reading-writing-grammar, students implemented changes in their texts regarding the use of the mechanisms that had been studied in class. They can be summarized as follows: a) there was an increase in the use of synonymous expressions, which are scarcely used by children in the first grades (CLARINDO, 2005); b) there was a decrease in the use of identical lexemes, which are commonly used by students because they are a reference mechanism that only involves repetition; and c) there was not any quantitative change in the use of the ellipsis but there was qualitative improvement in its use. Students‟ reports also show that a pedagogical proposal based on the integration of reading-writing-grammar in Portuguese classes may develop a privileged space for doubts and reflection upon how language works.